2022
DOI: 10.1128/aem.01595-21
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Fe(II)-Oxidizing Mechanisms in a Facultative Fe(II) Oxidizer, Sideroxydans lithotrophicus Strain ES-1, via Culturing, Transcriptomics, and Reverse Transcription-Quantitative PCR

Abstract: Sideroxydans lithotrophicus ES-1 grows autotrophically either by Fe(II) oxidation or thiosulfate oxidation, in contrast to most other neutrophilic Fe(II)-oxidizing bacteria (FeOB) isolates. This provides a unique opportunity to explore the physiology of a facultative FeOB and constrain the genes specific to Fe(II) oxidation. We compared the growth of S. lithotrophicus ES-1 on Fe(II), thiosulfate, and both substrates together. While initial growth rates were similar, thiosulf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 71 publications
2
42
0
Order By: Relevance
“…It is proposed that the unusual features of this protein, including the bis-His coordination of the heme and the fact that the heme is more exposed to the solvent when compared with other monoheme cytochromes, allows it to be sensitive to changes in the local environment, which enables it to function as an electron donor for cytochrome bc 1 , cytochrome bb 3 and CymA ES-1 [105]. Recently, a cultured-based study associated with transcriptomics assays also demonstrated that the cytochrome Cyc2 participates in the Fe(II) oxidation process [106]. Cyc2 is predicted to be a transmembrane beta barrel protein with an N-terminal cytochrome-like region [107].…”
Section: Extracellular Electron Transfer Processes Of Sideroxydans Li...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is proposed that the unusual features of this protein, including the bis-His coordination of the heme and the fact that the heme is more exposed to the solvent when compared with other monoheme cytochromes, allows it to be sensitive to changes in the local environment, which enables it to function as an electron donor for cytochrome bc 1 , cytochrome bb 3 and CymA ES-1 [105]. Recently, a cultured-based study associated with transcriptomics assays also demonstrated that the cytochrome Cyc2 participates in the Fe(II) oxidation process [106]. Cyc2 is predicted to be a transmembrane beta barrel protein with an N-terminal cytochrome-like region [107].…”
Section: Extracellular Electron Transfer Processes Of Sideroxydans Li...mentioning
confidence: 99%
“…S. lithotrophicus ES-1 contains three cyc2 genes that are adjacent to one another in the genome, and that are more expressed than mtoA in Fe(II)-citrate cultures. Besides cyc2 genes, there are other putative Fe(II) oxidation related genes that were overexpressed, including two periplasmic monoheme cytochromes and a gene cluster composed by five proteins, although their function remains to be elucidated [106].…”
Section: Extracellular Electron Transfer Processes Of Sideroxydans Li...mentioning
confidence: 99%
“…The presence of multiple EET pathways, and modularity of certain components may provide growth/survival advantages to S. lithotrophicus ES-1 under dynamic redox conditions, analogous to how Geobacter sulfurreducens has evolved distinct EET pathways based on redox potential and utilizing different soluble and insoluble sources and/or sinks of electrons in the environment [4,23]. Recent work quantifying expression of genes encoding candidate iron oxidation pathway genes from S. lithotrophicus found that paralogues of cyc2, encoding a protein recently shown to exhibit Fe(II) oxidation activity from M. ferrooxydans [24], were expressed highly mtoA under iron-and non-iron oxidizing conditions [25]. These results suggest that Cyc2, and not Mto, is the major pathway for Fe(II) oxidation in S. lithotrophicus under the conditions tested [25] and that more work should be done to investigate the role of Mto in EET.…”
Section: Inner Membrane and Periplasmic Components Of The Mto And Sli...mentioning
confidence: 99%
“…Recent work quantifying expression of genes encoding candidate iron oxidation pathway genes from S. lithotrophicus found that paralogues of cyc2, encoding a protein recently shown to exhibit Fe(II) oxidation activity from M. ferrooxydans [24], were expressed highly mtoA under iron-and non-iron oxidizing conditions [25]. These results suggest that Cyc2, and not Mto, is the major pathway for Fe(II) oxidation in S. lithotrophicus under the conditions tested [25] and that more work should be done to investigate the role of Mto in EET. In conclusion, we established the electron transfer functionality, interactions and modularity of novel EET components from an Fe(II) oxidizing bacterium that is dependent on EET for its primary metabolism.…”
Section: Inner Membrane and Periplasmic Components Of The Mto And Sli...mentioning
confidence: 99%
“…Furthermore, this activation correlates with Mn(II) oxidation and MOB-449 biofilm development, suggesting that Mn(II) oxidation is used to gain energy and survive under adverse environmental conditions. Previous studies in iron-oxidizing Zetaproteobacteria and other neutrophilic Fe-oxidizers have shown that the membrane c-type cytochrome Cyc2 and cytochrome c terminal oxidases are highly expressed in Fe(II)-rich environments and their expression is also stimulated by Fe(II) addition to bacterial cultures (Jewell et al, 2016;McAllister et al, 2020;Zhou et al, 2022). These results, in agreement with our results in MOB-449, suggest a transcriptional regulation mediated by Fe(II) and Mn(II) to allow the electrons derived from their oxidation reactions to be passed through cytochrome c terminal oxidases to reduce oxygen and acquire energy for growth (Jewell et al, 2016;McAllister et al, 2020;Zhou et al, 2022).…”
Section: Accession Descriptionmentioning
confidence: 99%